Investigating Translation Technique: A Result of the Students’ Work on Subtitling for the Deaf and Hard of Hearing - Aminudin, Muhammad Fauzan; Hidayati, Anni Nurul (Universitas Negeri Semarang, 2021)
The modern era, especially in the global pandemic Covid – 19, the need of information, knowledge and entertainment becomes a crucial part since the activities must go online. The government rule stated that the information shall be accessible for anyone, the deaf and hearing impaired, for instance. This descriptive qualitative study aims to investigate the translation technique done by the students in working for subtitling for the deaf and hard of hearing (SDH) in Audiovisual translation class. The finding of 208 data revealed that there are 12 of 18 techniques applied proposed by Molina and Albir. The most dominant technique is literal translation, besides it showed that the students as a subtitlers may apply one or more techniques during doing the subtitling. As a pedagogical implication to this study, the results can be considerations in designing the curriculum for Audio visual translation subject with complete theories and practices, especially in terms of building the emotion and characterization